Evidence-Based Management Approach In Health Service Policy Decision-Making At Clinic of Plantation Company X - Hidayat, Asep; Wardani, Ratna; Agustin (Health & Medical Sciences, 2025)
The research comprehensively examines the application of Evidence-Based Management (EBMgt) in decision-making for health service policies at Clinic of Plantation Company X. The main focus is on the influence of six types of evidence: Scientific and Research Evidence, Hospital Facts and Information, Political-Social Development Plans, Professional Managerial Expertise, Ethical-Moral Evidence, and Stakeholder Values and Expectations on policy decisions in the clinic. This study uses a quantitative method with a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). Data were collected through structured questionnaires from 110 respondents comprising managers and decision-makers at the clinic. Instrument validity and reliability were tested before conducting the measurement and structural model analysis. The findings show that all six evidence dimensions significantly affect policy decision-making (p < 0.05). The measurement model met convergent and discriminant validity criteria with AVE and composite reliability values above 0.70. Integrating these evidence dimensions enhances the quality, effectiveness, and accountability of managerial decisions at the clinic. The research highlights the importance of a holistic EBMgt approach combining empirical data, professional expertise, and ethical-social aspects to support effective and responsible policy decisions in healthcare services. The study recommends strengthening the use of multiperspective evidence in clinic policy management to achieve better and sustainable service outcomes.